Analisis Penyebab Kelainan Dan Upaya Mencegah Kelainan Berkebutuhan Khusus - niranti, karmila alia; yanti, melda; ulva, maria; Andriani, opi (Program Studi Pendidikan Vokasi Seni Kuliner, 2026)
The causes of disorders in children with special needs (ABK) come from various factors, including genetics, complications during pregnancy and childbirth, and exposure to poor environments, all of which require serious attention for prevention and early intervention. Significant gaps are found in inclusive education, where access to facilities, special educators, and financial support for ABK families is still very limited, especially in remote areas. The social stigma attached to ABK is a major obstacle to the acceptance and development of their potential, so a public awareness campaign is needed to create a more inclusive environment. Although legal protection has been regulated in Law Number 8 of 2016, its implementation has not been evenly distributed, and legal advocacy for ABK and their families is still lacking. Therefore, synergy is needed between families, communities, and the government to overcome these challenges, so that ABK rights can be optimally fulfilled and they can develop into empowered individuals.